Real-world outcomes of chemotherapy plus immune checkpoint inhibitors versus chemotherapy alone in advanced, unresectable, and recurrent intrahepatic cholangiocarcinoma - Madzikatire, Tinotenda Blessing; Heng, Shan; Gu, HongYi; Shan, YunFeng; Lin, EnHua; Banda, Joshua; Debora, Asta; Madziva, Brandon Anotida; Bowa, Mutale Jaeste; Mudhuri, Munyaradzi Godfrey; Bwalya, Canol (Frontiers in Immunology, 2024)
There are limited treatment options available to improve the prognosis of patients with advanced or metastatic cholangiocarcinoma particularly intrahepatic cholangiocarcinoma (iCCA). This study aimed to evaluate the efficacy and safety of combining chemotherapy plus anti-PD-1/L1 drugs compared to chemotherapy alone in advanced, unresectable, and recurrent intrahepatic cholangiocarcinoma patients.Patients with advanced, unresectable, or recurrent iCCA who received chemotherapy combined with PD-1/PD-L1 inhibitors or chemotherapy alone were retrospectively screened and analyzed. The primary outcomes were overall survival (OS) and progression-free survival (PFS). The secondary outcomes were overall response rate (ORR), disease control rate (DCR), and safety.81 eligible patients were included in the study (chemotherapy plus anti-PD-1/L1 group n=51, and chemotherapy-alone group n=30). The median OS was 11 months for the chemotherapy plus anti-PD-1/L1 group, significantly longer than the 8 months in the chemotherapy-alone group, with a hazard ratio (HR) of 0.53 (95% CI 0.30-0.94, P = 0.008). The median PFS of 7 months in the chemotherapy plus anti-PD-1/L1 group was significantly longer than the 4 months in the chemotherapy-alone group, with HR of 0.48 (95% CI 0.27-0.87); P = 0.002). Similarly, the combined therapy group showed a higher ORR (29.4%) and DCR (78.4%) compared to 13.3% and 73.3% in the chemotherapy-alone group, respectively. More grade 3-4 treatment-related adverse effects were recorded in the chemotherapy plus anti-PD-1/L1 group (66.7%) compared to the chemotherapy-alone group (23.3%), however, they were manageable and tolerable.Chemotherapy plus anti-PD-1/L1 represents a more effective and tolerable treatment option for advanced, unresectable, and recurrent iCCA patients compared to chemotherapy alone.